NIEPRZEMIJAJĄCY UROK KRESÓW, CZYLI XVII-WIECZNA UKRAINA W POWIEŚCI FANTASTYCZNO-HISTORYCZNEJ JACKA KOMUDY WILCZE GNIAZDO - Dejnek, Katarzyna Anna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article presents Borderlands’ thread in the historical fantasy novel Wolves’ nest by jacek Komuda. it focuses on showing the awareness of the border, where the protagonists live. The article starts with a short presentation of the author’s profile and his literary achievements. Next, basic information about the theme of Borderlands in Polish literature and the source of their attractiveness and popularity is discussed. The main part of the article is the analysis of Borderlands’ threads in the novel along with the presentation of the 17th century Ukraine, their citizens as well as their culture and customs. it delivers detailed information about the image of Ukraine and the cultural awareness of its habitants constructed by Komuda.